2005
DOI: 10.1681/asn.2004110999
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilia and the Risk for Hemodialysis Vascular Access Thrombosis

Abstract: Vascular access thrombosis is the most common and costly complication in hemodialysis patients. The role of thrombophilia in access thrombosis is not established. A case-control study was conducted of 419 hemodialysis patients to determine whether thrombophilia was associated with arteriovenous fistula or graft thrombosis. Participants were enrolled from three in-center and five satellite dialysis units associated with a Canadian academic health science center that provides dialysis services in a catchment are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 46 publications
(54 reference statements)
6
83
0
1
Order By: Relevance
“…Antiphospholipid antibodies were more common in men but did not seem to affect the AVF outcome. High incidence of thrombophilia is reportedly associated with risk of thrombosis after access surgery or revascularization among patients with ESRD and those with other vascular conditions (2,11,14). The difference in thrombophilia prevalence among the studies reflects various definitions of thrombophilia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antiphospholipid antibodies were more common in men but did not seem to affect the AVF outcome. High incidence of thrombophilia is reportedly associated with risk of thrombosis after access surgery or revascularization among patients with ESRD and those with other vascular conditions (2,11,14). The difference in thrombophilia prevalence among the studies reflects various definitions of thrombophilia.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the United States the annual costs of access failure are approximately $1 billion (1). The main causes of access dysfunction-thrombosis and stenosisare associated with vascular injury and intimal hyperplasia caused by high-shear-rate conditions in the access (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Thrombophilic risk factors were moderately associated with access thrombosis (OR < 3) in a case control study by Knoll. 39 FVL, elevated factor VIII levels, elevated homocysteine and elevated lipoprotein (a) were associated with excess thrombosis. Overall 55% of patients with access thrombosis had one thrombophilic defect and for each additional thrombophilic defect the odds of thrombosis increased significantly, OR 1.87.…”
Section: Hemodialysis Vascular Access Thrombosismentioning
confidence: 97%
“…Several studies have reported associations between hereditary hypercoagulable disorders, elevated homocysteine levels and antiphospholipid antibodies and increased frequency of ac-cess thrombosis. 39 In a small retrospective series by LeSar et al 40 42% of 67 thrombotic events reviewed were associated with thrombophilic disorders without an identified anatomic vascular stenosis and an additional 19% of events were associated with thrombophilia in the presence of vascular stenosis. Presence of a lupus anticoagulant was found in 16.5% of 97 patients with end-stage renal disease and was associated with a higher frequency of access thrombosis (62% vs 26%).…”
Section: Hemodialysis Vascular Access Thrombosismentioning
confidence: 98%